Ecological Perspectives on Teaching Arabic as a Foreign Language: Exploring Interactions among Learners, Teachers, and Learning Environments / المنظورات البيئية في تعليم اللغة العربية لغةً أجنبية: استكشاف التفاعلات بين المتعلمين والمعلمين والبيئات التعليمية - Muhammad Ridwan; Aisyah Binti Ustman (IJAS: International Journal of Arabic Studies, 2026)
This study explores the ecological interactions among learners, teachers, and learning environments in Teaching Arabic as a Foreign Language (TAFL) through an ecological perspective. The study employed a qualitative approach using an ecological case study design. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings reveal that interactive learning environments significantly enhance learners’ motivation, participation, and language development. Teachers play a crucial role in creating supportive and engaging learning environments that facilitate meaningful interaction. The study also highlights the importance of social interaction, digital resources, cultural diversity, and institutional support in shaping Arabic language learning experiences. Furthermore, the results demonstrate that learning Arabic as a foreign language is a dynamic ecological process involving continuous interactions among multiple elements within the educational environment. The study recommends developing Arabic language curricula based on ecological principles that emphasize interaction, collaborative learning, and technology integration. Future studies are encouraged to investigate ecological factors in various educational contexts.